Profit Distribution Management Determinant (Empirical Study in Indonesian Sharia Banks) - Ardiani Ika Sulistyawati; Aristi Aprilia Asmaraputri; Aprih Santoso (Jurnal Ilmiah Ekonomi Islam, 2019)
The purpose of this research is to know the factors affecting to profit distribution management of Sharia Banks in Indonesia on the period 2013 until 2016. Variabel dependent of this research is profit distribution management. While the independen of this research is capital adequancy, effectiviness of third party funds, financial risk, gross domestic of product growth, propotion of investment financial, proportion of third party funds, loss of earning assets, age of bank, BOPO, Bi-rate. This research use sharia banks which registered in Bank Indonesia on 2013 until 2016 period. Collecting data of this research use purposive sampling method. The test data analysis use classic assumption test, hypothesis test, and data analysis of multiple regression. The result of the hypothesis test is that capital adequancy, effectiveness of third party funds, financial risk, loss of earning assets, BOPO and Bi rate have no effect to profit distribution management. While gross domestic of product growth, proportion of investment, proportion of third party funds and age of bank have the effect of profit distriburion management. Keywords : Profit, Financial, Risk, Investment